2021
DOI: 10.21837/pm.v19i16.957
|View full text |Cite
|
Sign up to set email alerts
|

Brownfield Sites and Property Market Sensitivity

Abstract: The existence of Brownfield sites is one of the main challenges that Malaysia must face due to financial, administrative and policy problems. The negative environmental and social impacts of Brownfield sites jeopardise residents’ health and well-being, causing nearby areas to be less desirable for occupation and investment. These impacts result in price discounts. Hence, this research aims to establish the sensitivity of the property market towards Brownfield sites through a critical review. An overview of pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…The negative (environmental and social) effects of brownfields jeopardise residents' health and well-being, by making close areas less attractive for employment and investment, and determining selling price discounts. Zihannudin et al [62] carried out extensive studies on the property market sensitivity to brownfield sites through a critical review of previous relevant researches. They confirmed that the proximity to a brownfield site constitutes a factor considered in property purchase decisions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The negative (environmental and social) effects of brownfields jeopardise residents' health and well-being, by making close areas less attractive for employment and investment, and determining selling price discounts. Zihannudin et al [62] carried out extensive studies on the property market sensitivity to brownfield sites through a critical review of previous relevant researches. They confirmed that the proximity to a brownfield site constitutes a factor considered in property purchase decisions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Short traveling distances between home, work, and leisure were achieved on both sites. Location is a critical factor for developers as the location of a property influences purchase decisions, which then reflects property prices with buyers willing to pay premium prices for desirable locations (Zihannudin et al, 2021). Developments in prime locations represent a lower risk for developers to secure funding and realize sales (Syms, 1999).…”
Section: Economic Considerations Contributing To the Decision-makingmentioning
confidence: 99%